Doktrin Business Judgement Rule pada Bank dengan Prinsip Syariah - Andi Fariana; Mohammad Wimbo Raksadigiri; Saripudin Saripudin (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The Board of Directors is one of the organs of a Limited Liability Company which has great duties, responsibilities and authority in managing the company, as well as directors of Islamic banks whose legal entity is also a Limited Liability Company. In carrying out their duties, the directors may take actions that result in losses for the company, and for this the directors must be held accountable. However, the business judgment rule doctrine suggests that the board of directors may not be held responsible for the company's losses as a result of its management as long as the board of directors is proven to have managed it in good faith and in accordance with the company's Articles of Association. For directors at Islamic banks, this doctrine is only one of the reasons that can cause directors to act professionally without fear of being wrong. In addition to the doctrine, the existence of the Sharia Supervisory Board (DPS) and commissioners is important because they participate in supervising and providing advice on the actions of the directors, and the main thing above all is the belief in the existence of divine accountability, all of which become one unit which in the end can give rise to actions that are solely for the benefit of the company and welfare. Keywords: Board of Directors, business judgment rule, Islamic bank